A BLUEPRINT FOR EPA: HOW THE AGENCY CAN OVERCOME THE STATUTE OF LIMITATIONS WHEN ENFORCING PSD UNDER THE CLEAN AIR ACT (Utah Environmental Law Review; Vol 31 No 1 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} This Article presents three legal theories that the Environmental Protection Agency (EPA) could employ in order for it to effectively enforce the Prevention of Significant Deterioration (PSD) requirements for stationary sources under the Clean Air Act (CAA) when the PSD violations are arguably beyond the five-year statute of limitations. In doing so, the Article explores various hurdles EPA would encounter. It also presents legal and policy arguments explaining why the courts should allow EPA to enforce PSD despite the statute of limitations.